IMPLEMENTASI PEMBELAJARAN BERBASIS KOMPUTER MENGGUNAKAN SOFTWARE GEOGEBRA TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK DI KOTA KUNINGAN - Ricki Yuliardi; M. Irfan Habibi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
The purpose of this study was to determine the effectiveness of learning Computer Assisted Instruction (CAI) Assisted by GeoGebra Software for communication capabilities mathematically students in Geometry transformation material. The population in this study is a class XI student of SMK 3 Kuningan academic year 2013/2014. Election The sample was purposed random sampling, in the selection of samples obtained XI-TSM 2 students as the experimental class and XI-TSM 4 class as the control class. The experimental class is taught by learning Computer Assisted Instruction (CAI) Assisted by GeoGebra Software, while the control class is taught with expository learning. Data retrieval was obtained by the results of the pretest and posttest to obtain data on the value of spatial abilities and mathematical communication skills of students which were then analyzed by a mean difference test. The results of the study were: (1) Improved mathematical communication skills of the experimental class students better than the control class. (2) There is a positive response between CAI learning developed